Analisis Morfologi pada Gaya Bahasa Mahasiswa 1E Pendidikan Guru Madrasah Ibtidaiyah - muhammad Muhammad tibi (Jurnal Lazuardi, 2026)
This study aims to describe morphological processes including affixation, reduplication, and compounding in the language style of 1E students of Madrasah Ibtidaiyah Teacher Education (PGMI). This research employed a qualitative descriptive method. The data were words and phrases containing morphological processes found in students’ academic writings such as essays and course reports. The data sources were written assignments of 1E PGMI students. Data collection techniques included documentation, observation, and note-taking. Data analysis was conducted using the flow model of analysis consisting of data reduction, data display, and conclusion drawing. The results showed that (1) the forms of affixation used by students included prefixes, suffixes, and confixes, with prefixes meN-, ber-, and di- being the most dominant. Some errors were found, especially in the use of di- and meN- prefixes. (2) The forms of reduplication found were full reduplication and affixed-base reduplication, with minor writing errors. (3) The forms of compounding consisted of compound nouns, compound verbs, and compound adjectives, with compound nouns being the most frequently used.